Homenaje a J. A. van Praag. 1930-1935. Librería Española "Plus Ultra", Amsterdam, [1956]; 164 pp. - Alatorre, Antonio (El Colegio de México, 1962)
Se reseñó  el libro: Homenaje a J. A. van Praag. 1930-1935.